Δr in the Two-Higgs-Doublet Model at full one loop level - and beyond - López-Val, David; Solà Peracaula, Joan (The European physical journal. C, Particles and fields, 2013)
After the recent discovery of a Higgs-like boson particle at the CERN LHC-collider, it becomes more necessary than ever to prepare ourselves for identifying its standard or non-standard nature. The fundamental parameter Δr, relating the values of the electroweak gauge boson masses and the Fermi constant, is the traditional observable encoding high precision information of the quantum effects. In this work we present a complete quantitative study of Δr in the framework of the general Two-Higgs-Doublet Model (2HDM). While the one-loop analysis of Δr in this model was carried out long ago, in the first part of our work we consistently incorporate the higher order effects that have been computed since then for the SM part of Δr. Within the on-shell scheme, we find typical corrections leading to shifts of ∼20-40 MeV on the W mass, resulting in a better agreement with its experimentally measured value and in a degree no less significant than in the MSSM case. In the second part of our study we devise a set of effective couplings that capture the dominant higher order genuine 2HDM quantum effects on the δρ part of Δr in the limit of large Higgs boson self-interactions. This limit constitutes a telltale property of the general 2HDM which is unmatched by e.g. the MSSM.